Integrated Cost–Durability Assessment of Waste Glass Aggregate Concrete with ASR Mitigation for Sustainable Construction in Indonesia - Endah Murtiana Sari; Probokusumo Probokusumo; Alfiya Rokhmah; Rahmat Rahmat; Muhamad Dzaky Ashidqi (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2026)
This study presents an integrated assessment of the economic, technical, and environmental feasibility of incorporating waste glass aggregate (WGA) as a partial replacement for natural coarse aggregate in concrete within the Indonesian construction context. A simulation-based framework using secondary data was employed, combining quantitative cost analysis with a systematic synthesis of experimental studies published between 2023 and 2025. No primary laboratory experiments were conducted. The cost analysis indicates that replacing 30% of natural coarse aggregate with WGA reduces the estimated concrete production cost from IDR 905,000/m³ to IDR 873,000/m³, corresponding to an estimated cost saving of approximately 3.5% under representative Indonesian material prices. Synthesized experimental evidence further indicates that concrete incorporating 30% WGA can maintain a 28-day compressive strength of approximately 35–40 MPa when appropriate mixture design is adopted. The incorporation of supplementary cementitious materials, including 25% fly ash and 20% ground granulated blast furnace slag (by mass of total binder), has been reported to mitigate alkali–silica reaction (ASR), reducing expansion by up to approximately 70% while improving resistance to chloride ingress. Published life-cycle assessment studies also indicate potential reductions of approximately 11% in carbon dioxide (CO₂) emissions and 15% in cumulative energy consumption relative to conventional concrete. The integrated assessment suggests that WGA concrete offers promising economic, technical, and environmental benefits and may represent a viable alternative construction material to support sustainable construction and circular economy initiatives in Indonesia.